Evaluation of nutmeg (Myristica fragrans Houtt) as active component during storage of bovine loins - Galeano L., Yessica; Torres V., Olga; García S., Ángela (Revista de Ciencias Agrícolas, 2018)
Meat products are considered highly perishable foods because of their physical, chemical and biological characteristics. Different compounds can be combined to produce active films with greater functionality, which can provide effective protection to food during storage. In this research, active films formulated with polyvinyl alcohol, gelatin, and different oleoresin concentrations of nutmeg (Myristica fragrans) were made by using the casting methodology, a process by which a solution is poured into a mold. Bovine loins (Longissimus dorsi) were coated with the active films formulated, stored at 4 °C, performing physicochemical characterization for 1, 3, 6 and 10 days. The results obtained indicate a decrease in pH, humidity percentage, peroxide value (POVs), total volatile nitrogen bases (TVB-N) and greater conservation of the a* parameter (coordinate where +a indicates red, -a indicates green) in loins covered with active films during storage time. Thus, the active films formulated could be used in the meat industry to extend the shelf life of bovine loins.